Cerebral infarction: an unusual manifestation of viper snake bite - Pal, Jyotirmoy; Mondal, Sumantro; Sinha, Debanjali; Ete, Tony; Chakraborty, Atanu; Nag, Arijit; Sarkar, Gouranga; Saha, Bikram (International Journal of Research in Medical Sciences, 2017)
Snake envenomation causes significant mortality and morbidity. Viper bite usually present with local cellulites, renal failure and bleeding disorders. Thrombotic manifestation of snake bite is rarely reported and early administration of Anti-Snake Venom Serum (ASV) also reduces the risk of thrombotic complications. Cerebral infarction in case of viper bite may be due to hypotension, hypercoagulability or direct action of venom on vessel wall. We report a rare case of viper bite, presented with renal failure and cerebral infarction in spite of early ASV institution. The thrombotic manifestation in this case was possibly due to disseminated intravascular coagulation.